Assessment of Human-Tiger Conflict and its Community Based Mitigation Efforts in Madi Valley of Chitwan District, Nepal - Dahal, Sita; Thanet, Dol Raj; Gautam, Deepak (Journal of Forest and Natural Resource Management, 2020)
Human fatalities and livestock depredation are the ultimate manifestation of human–tiger conflict (HTC). It is one of the major challenging issues that need to be sorted out where such incidences occur frequently. This study aimed to investigate the status of HTC and mitigation measures adopted by local communities in Madi valley adjacent of Chitwan National Park (CNP). Data were collected through household interviews (n=52, including 25% victim’s households), direct field observation and CNP archive records from 2014 to 2018. This study revealed that average livestock depredation was 15.60 (n=78, mean=5.06, SE±1.66) animals per year and among them goats were highly depredated animals (n=39, mean=7.80, SE±2.33). It also showed that livestock depredation trend increased at the rate of 4.1 animals per year but that of human casualties decreased at the rate of -0.3 persons per year during 2014 to 2018. Predation proof corrals, mesh wire fencing, traditional fencing using white cloths andlivelihood diversifications were the major local mitigation efforts adopted by local people. However, detailed studies on effectiveness of locally adopted mitigation techniques along with further investment to implement them from government line agencies and conservation partners are suggested for strengthening human-tiger co-existence in the study area.